Mechanism of inhibition on L929 rat fibroblasts proliferation induced by potential adhesion barrier material poly(p‐dioxanone‐co‐l‐phenylalanine) electrospun membranes. Issue 11 (17th January 2014) - Wang, Bing; Dong, Jun; Li, Qijie; Xiong, Zuochun; Xiong, Chengdong; Chen, Dongliang
Abstract Fibroblast plays an important role in the occurrence of postoperative tissue adhesion; materials that have particular "cell–material" interactions to inhibit proliferation of fibroblast will be excellent potential adhesion barriers. In the current study, we synthesized copolymers of p‐dioxanone and l‐phenylalanine (PDPA) and evaluated the mechanism of its particular inhibition effect on L929 fibroblast proliferation when used as a culture surface. PDPA electrospun membranes could induce apoptosis of L929 fibroblasts. We hypothesized there were two reasons for the apoptosis induction: one was the ability to facilitate cell adhesion of materials, and the other was production of the degradation product, l‐phenylalanine. Ninhydrin colorimetric results revealed that l‐phenylalanine was continuously released during the culture process and could induce apoptosis in L929 cells. Relatively poor cell adhesion and constant release of l‐phenylalanine made PDPA‐1 to be the most efficient polymer for the induction of apoptosis. Analysis of apoptosis‐related genes revealed that PDPA‐induced apoptosis might be performed in a mitochondrial‐dependent pathway. But poly(p‐dioxanone)‐induced apoptosis might occur in a c‐Myc independent pathway that was different from PDPA. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4062–4070, 2014.